Method for testing adhesive force of polyester film by using UV ink coating

Through UV ink and laser engraving technology, combined with vacuum coating and UV light curing, the problems of low adhesion testing efficiency and inaccurate results of polyester film ink are solved, and fast and accurate adhesion evaluation is achieved, which improves production efficiency and Reduces harm to the human body.

CN119147458APending Publication Date: 2024-12-17TIANJIN WANHUA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411582646.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The prior art has problems of low efficiency, inaccurate test results and potential harm to the human body when testing the adhesion of polyester film inks. In particular, the color paint and varnish test methods are not suitable for thick coatings and contain volatile organic compounds.

Method used

UV ink combined with vacuum coating, UV light curing and laser engraving technology, quickly evaluate the ink adhesion by drawing lattice patterns on polyester films and peeling them with 3M tape, avoiding the limitations and potential hazards of traditional testing methods.

Benefits of technology

It improves testing efficiency, reduces production cycle, accurately identifys adhesion defects, and promptly feedback to the front end of the production, improves production efficiency, reduces testing costs and harm to the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119147458A_ABST
    Figure CN119147458A_ABST
Patent Text Reader

Abstract

The invention discloses a method for testing the adhesive force of a polyester film by using a UV ink coating. The surface of the polyester film is uniformly coated with UV ink by using a winding bar / blade coating machine. And then fixing the polyester film coated with the UV printing ink on a substrate of a light curing machine, and placing the polyester film in the UV light curing machine for curing treatment. And after the UV ink is completely dried and firmly attached to the surface of the polyester film, taking out the polyester film from the curing machine. And engraving a cross-grid pattern on the surface of the polyester film coated with the UV ink by using a laser engraving machine, and then completely covering the cross-grid pattern by using a 3M adhesive tape. Subsequently, the adhesive tape is quickly torn off with a constant force by a peeling machine. By observing the proportion of the number of the grids taken away by the adhesive tape to the total number of the grids, the adhesive force grade of the UV ink on the polyester film can be evaluated. According to the invention, the processes of ink adhesion testing, ink curing parameter adjustment, defective product formula adjustment and the like are completed in one step, and the actual production efficiency is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester film testing, in particular to a method for testing the adhesion of a polyester film by printing with UV ink. Background Art

[0002] Compared with traditional paper labels, film label materials have many advantages such as water resistance, wear resistance, corrosion resistance, strong tear resistance, high transparency, and strong weather resistance. They are widely used in electronics, food, medicine, fast-moving consumer goods and other fields. Therefore, the quality, processing and printing, and functional applicability of film label paper play a vital role in the quality of labels. Polyester film has excellent mechanical properties, high strength, friction resistance, high temperature resistance, chemical resistance, oil resistance, etc. It is one of the commonly used film materials for labels. In the actual production process, polyester film manufacturers usually send polyester films to downstream customers for printing inks, and then conduct ink adhesion tests. If the ink adhesion is poor, it will be returned to the polyester film manufacturer for formula process adjustment, which will greatly reduce production efficiency. Before sending polyester film to downstream customers for printing inks, how to obtain its adhesion data and adjust the formula to improve production efficiency is an urgent problem to be solved.

[0003] There are currently two main test methods for coating adhesion: the cross-cut test for paint and varnish films (GB / T 9286-2021) and the pull-off adhesion test for paint and varnish (GB / T 5210-2006).

[0004] The cross-cut test for paint and varnish film (GB / T 9286-2021) is a test method that uses a cutting tool to cut the coating in a right-angle grid pattern and penetrate to the substrate to evaluate the resistance of varnish and paint coating to detach from the substrate. Although this test method is widely used, it is limited by the test tools and cutting techniques. In addition, this test method stipulates that it is not applicable to coatings with a total thickness greater than 250μm, which has great limitations in actual production. The pull-off adhesion test for paint and varnish (GB / T 5210-2006) is a test method for measuring adhesion by performing a pull-off adhesion test on a single coating or multi-coating system of paint, varnish or related products. This test method expresses the test results by the tensile force between the destruction interfaces (adhesion failure) or the tensile force of self-destruction (cohesive failure), so adhesion / cohesive failure is likely to occur simultaneously, making it inconvenient to judge whether the loss is cohesion or adhesion. In addition, the above two test methods are based on paint and varnish coatings. Its curing time increases with the thickness of the coating, resulting in a slow test result acquisition speed. In addition, some polyester film surfaces will react chemically with paints and varnishes after treatment, resulting in inaccurate adhesion test results. At the same time, paints and varnishes usually contain a certain amount of volatile organic compounds, which will cause potential harm to the human body during the test process. Summary of the invention

[0005] In view of the above problems, the present invention provides a method for testing the adhesion of polyester film using UV ink coating, which utilizes the characteristics of UV ink that can be quickly cured and dried almost instantly under ultraviolet light to improve test efficiency and reduce test waiting time.

[0006] The present invention provides the following technical solution: a method for testing the adhesion of a polyester film using a UV ink coating, comprising the following steps:

[0007] (1) Select a clean polyester film and cut it into A4 size;

[0008] (2) Start the vacuum pump, fix the polyester film on the online rod / scraper coater using vacuum adsorption technology and set the coater parameters: the rod / scraper height range is 1 to 1000 μm, the scraping speed is 1 to 10 mm / s, the UV ink is evenly poured on the front end of the online rod / scraper, and the coater is started to start coating;

[0009] (3) fixing the polyester film coated with UV ink in step (2) on a substrate of a UV curing machine, placing the film in the UV curing machine for curing, and taking the film out of the curing machine after the UV ink is completely dried;

[0010] (4) setting the hundred-grid engraving parameters in the program of the laser engraving machine, and placing the polyester film coated with UV ink in step (3) on the machine table of the laser engraving machine for hundred-grid engraving;

[0011] (5) After engraving is completed, 3M tape is evenly applied to the polyester film on which the 100 grids are engraved in step (4) and allowed to stand; then, a peeling machine is used to quickly peel off the grids with a constant force, and the adhesion level of the UV ink on the polyester film is evaluated by observing the ratio of the number of grids removed by the tape to the total number of grids.

[0012] Furthermore, in step (2), the experimental temperature is 15-30° C. and the relative humidity is 40%-60%.

[0013] Furthermore, the specific steps of the hundred-grid engraving method used in step (4) are as follows: a hundred-grid pattern is designed in the software of the laser engraving machine, the pattern consisting of ten horizontal lines and ten vertical lines, and the spacing between each line is uniform and is 0.5 to 2 cm; the depth of the line engraving is the same as the thickness of the scraping to avoid scratching the polyester film, and finally a grid of 10×10 in the horizontal and vertical directions is formed, containing a total of 100 grids.

[0014] Furthermore, the steps of the tape sticking and peeling process in step (5) are as follows: stick the 3M tape parallely and evenly on the cured UV ink polyester film, ensuring that the middle of the tape completely covers the squares of the hundred-grid engraving; use an eraser to wipe the tape to apply pressure to ensure that it is evenly pasted and there is no air underneath; after pasting is completed, wait for 30 to 120 seconds to ensure that the tape and the film are fully bonded; use the clamp of the peeling machine to fix the free end of the tape and the polyester film not coated with UV ink, and quickly remove the tape at an angle of 180° and apply a force of 150 to 200N.

[0015] Furthermore, in step (5), the tape is one of 3M600, 3M610, Nichiban Tape, and P99 Tape. To avoid errors, the same batch of tape is used in each experiment.

[0016] Furthermore, in step (3), the UV curing machine is preheated for 15 to 90 seconds before use, and the polyester film coated with UV ink is placed in the UV curing machine for curing 1 to 3 times until the UV ink is completely dry.

[0017] Furthermore, in step (3), the final thickness of the ink coating is 10 to 100 μm.

[0018] Further, in step (5), the adhesion grade evaluation criteria are as follows:

[0019] 5B grade polyester film: There is no shedding of UV ink on the edges of all grid areas;

[0020] 4B grade polyester film: UV ink on the edges of the grids in the grid area has peeling phenomenon, and the peeling rate is ≤5%;

[0021] 3B grade polyester film: UV ink on the edges of the grids in the grid area has peeling phenomenon, 5%<peeling ratio≤15%;

[0022] 2B grade polyester film: large pieces of UV ink fell off at the edges of the grids in the grid area, and some grids fell off in pieces, with a shedding ratio of 15% < ≤ 35%;

[0023] 1B grade polyester film: large pieces of UV ink fell off at the edges of the grids in the grid area and some grids fell off completely, with a shedding ratio of 35% < ≤ 65%.

[0024] The advantages and technical effects of the present invention are as follows: The method of the present invention simulates the printing process of an ink printer by combining a wire rod / blade coater with a UV light curing machine, adjusts the coating thickness over a wide range, quickly cures the UV ink, and shortens the production cycle. A hundred-grid pattern is accurately engraved on the coating with the help of a laser engraving machine. This process effectively eliminates the influence of the tension generated by the film's own destruction on the adhesion test results. The method can quickly identify polyester films with defects during the adhesion test and provide timely feedback to the production front end for formula adjustment. The ink adhesion test, ink curing parameter adjustment, and defective product formula adjustment processes are completed in one step, thereby improving actual production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is an example of a laser engraving machine of the present invention marking a hundred-grid pattern. DETAILED DESCRIPTION

[0026] The testing method of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments, and cannot be used to limit the scope of the present invention.

[0027] The method for testing the adhesion of a polyester film using a UV ink coating of the present invention comprises the following steps:

[0028] Step 1. Select the clean polyester film in the middle of the large polyester film roll, cut it completely with a wallpaper knife, and then cut it into A4 size.

[0029] Step 2: Start the vacuum pump and fix the polyester film on the vacuum wire rod / scraper coater using vacuum adsorption technology. Adjust the equipment parameters, set the scraping thickness range to 1-1000μm and the scraping speed to 1-10mm / s. Pour the UV ink evenly on the front end of the wire rod / scraper, start the coater and start coating.

[0030] Furthermore, UV ink is sensitive to temperature and humidity, and changes in temperature and humidity will cause changes in its viscosity. Therefore, in order to ensure that the viscosity of the UV ink remains consistent in each test, the experimental temperature in step 2 is specified to be 15-30°C and the relative humidity is 40-60%.

[0031] Step 3: fix the polyester film coated with UV ink in step 2 on the substrate of the UV curing machine, and put it into the UV curing machine for curing. After the UV ink is completely dried, take it out of the curing machine.

[0032] Furthermore, in step 3, the UV curing machine is preheated for 15 to 90 seconds before use.

[0033] Furthermore, in step 3, the number of curing times is adjusted to 1 to 3 times according to the change in the thickness of the UV ink coating.

[0034] Step 4: Set the grid engraving parameters in the laser engraving machine program, and place the polyester film coated with UV ink in step 3 on the laser engraving machine for grid engraving.

[0035] Furthermore, the 100-grid pattern designed in the software of the laser engraving machine consists of ten horizontal lines and ten vertical lines, with the spacing of each line uniform and 0.5 to 2 cm. The depth of these lines engraved must be strictly the same as the coating thickness, eliminating the influence of the tension generated by the film's own destruction on the adhesion test results, and the engraving depth is 1 to 1000 μm. In this way, a grid of 10×10 in the horizontal and vertical directions is finally formed, containing a total of 100 grids.

[0036] Step 5: After engraving, apply 3M tape evenly to the polyester film engraved in step 4 and use a peeling machine to quickly peel it off with a constant force. By observing the ratio of the number of grids taken away by the tape to the total number of grids, the adhesion level of the UV ink on the polyester film can be evaluated.

[0037] Furthermore, the 3M tape in step 5 includes but is not limited to 3M600, 3M610, Nichiban Tape, and P99 Tape. To avoid errors, the same batch of tape should be used for each experiment.

[0038] Furthermore, the method for peeling off the 3M tape after pasting in step 5 is: stick the 3M tape parallely and flatly on the cured UV ink polyester film, ensuring that the middle of the tape completely covers the squares of the hundred-grid engraving. Use an eraser to wipe the tape to apply pressure to ensure that it is evenly pasted and there is no air underneath. After pasting, wait for 30 to 120 seconds to ensure full bonding between the tape and the film. Then, use the clamp of the stripping machine to fix the free end of the tape and the polyester film not coated with UV ink, and quickly remove the tape at an angle of 180° and apply a force of 150 to 200N.

[0039] Further, the adhesion grade evaluation standard described in step 5 is graded according to the test results described in the cross-cut test of paint and varnish film (GB / T 9286-2021): The UV ink peeling situation of the cross-cut area of ​​the polyester film of level 0 is: the cutting edge is completely smooth, and there is no peeling in the grid. The UV ink peeling situation of the cross-cut area of ​​the polyester film of level 1 is: a small amount of coating peeling off at the intersection of the cut, but the affected cross-cut area is not more than 5%. The UV ink peeling situation of the cross-cut area of ​​the polyester film of level 2 is: the coating peeling off at the intersection of the cut and / or along the edge of the cut, and the affected cross-cut area is greater than 5%, but not more than 15%. The UV ink peeling situation of the cross-cut area of ​​the polyester film of level 3 is: the coating partially or completely falls off in large fragments along the cutting edge and / or partially or completely falls off at different parts of the grid, and the affected cross-cut area is greater than 15%, but not more than 35%. The UV ink peeling condition of the polyester film with a grade of 4 is: large pieces of coating peeling off along the cut edge and / or some squares peeling off partially or completely, and the affected cross-cut area is greater than 35%, but not greater than 65%. The UV ink peeling condition of the polyester film with a grade of 5 is: the degree of peeling exceeds that of grade 4.

[0040] The present invention uses laser engraving technology to replace the traditional manual grid-punching method to test adhesion, which not only effectively avoids the influence of tension caused by self-destruction of the film on the test results, but also significantly reduces the time and cost required for testing, further improving the overall production efficiency.

[0041] Example: Adhesion test was performed on polyester films for printing from three different manufacturers, and the results were compared with the ink adhesion test results after printing by downstream customers. The operation steps are as follows:

[0042] (1) Select the clean parts of the middle layer of three large polyester film rolls, cut them off completely with a wallpaper knife, and then cut them into A4 sizes and name them polyester films No. 1, 2, and 3 respectively.

[0043] (2) Control the test temperature to 25°C and the relative humidity to 40%. Start the vacuum pump and use vacuum adsorption technology to fix the No. 1 polyester film on the vacuum wire rod / scraper coater. Adjust the equipment parameters and set the scraping thickness range to 500μm, the scraping speed to 2mm / s, and the scraping distance to 250mm. Pour the UV ink evenly on the front end of the wire rod / scraper, start the coater and start coating. A layer of UV ink coating with a thickness of 500μm and a length of 250mm can be formed on the surface of the No. 1 polyester film. After cleaning the scraper, apply a UV ink coating with a thickness of 500μm and a length of 250mm on the No. 2 and No. 3 polyester films in the same way.

[0044] (3) Turn on and preheat the UV curing machine for 30 seconds, then fix the polyester film coated with UV ink flatly on the base of the UV curing machine, and click the "Start" button to start curing. When the polyester film coated with UV ink comes out from the other end of the UV curing machine, the curing is completed. Repeat the above steps 3 times until the UV ink is completely dry. Use the same method to cure the UV ink of polyester films No. 2 and No. 3.

[0045] (4) Set the hundred-grid engraving parameters in the laser engraving machine program, design ten horizontal lines and ten vertical lines, the spacing between each line is uniform and 1 cm, the engraving depth is 500 μm, and a horizontal and vertical grid of 10×10 is formed, containing a total of 100 grids. Place the No. 1 polyester film after UV ink curing flat on the machine table of the laser engraving machine, set the engraving starting point, and click Start to start laser engraving. Use the same method to engrave the hundred-grid pattern on the No. 2 and No. 3 polyester films.

[0046] (5) Use 3M600 tape with a width of 19 mm and cut it into 18 strips of 12 cm in length, divided into three groups. Then stick them parallel and flat on the engraving area, use an eraser to wipe the tape to apply pressure to ensure that it is evenly pasted and there is no air underneath. Wait for 60 seconds after pasting.

[0047] (6) Use the clamp of the peeling machine to fix the free end of the No. 1 polyester film tape and the polyester film area not coated with UV ink, and quickly remove the tape at an angle of 180°, applying a force of 200N. Use the same method to peel off the free ends of the No. 2 and No. 3 polyester film tapes and the polyester film area not coated with UV ink. By observing the grid ratio of the three polyester films that are peeled off, the adhesion level of the three different manufacturers' printing polyester films can be judged.

[0048] (7) Compare the test results with the ink adhesion test results of downstream customers after printing. The results are shown in the following table:

[0049]

[0050] By comparison, it can be seen that UV ink coating used for polyester film adhesion test is simple to operate, time-saving and labor-saving compared to sending it to downstream customers for printing ink and then testing the adhesion. The ink adhesion test, ink curing parameter adjustment and defective product formula adjustment can be completed in one step, which improves the actual production efficiency. In addition, the test results of UV ink coating testing polyester film adhesion are not much different from those of downstream customers testing adhesion after printing ink. It provides a certain reference for the adhesion test of polyester film for labels in the future.

[0051] The above-described embodiments are only used to illustrate the technical solutions of the present invention, and their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. Any modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention still fall within the patent scope of the present invention.

Claims

1. A method for testing the adhesion of polyester film using UV ink coating, characterized in that: The steps include: (1) Select a clean polyester film and cut it into A4 size; (2) Start the vacuum pump, fix the polyester film on the online rod / scraper coater using vacuum adsorption technology and set the coater parameters: the rod / scraper height range is 1 to 1000 μm, the scraping speed is 1 to 10 mm / s, the UV ink is evenly poured on the front end of the online rod / scraper, and the coater is started to start coating; (3) fixing the polyester film coated with UV ink in step (2) on a substrate of a UV curing machine, and placing it in the UV curing machine for curing, and taking it out of the curing machine after the UV ink is completely dried; (4) setting the hundred-grid engraving parameters in the program of the laser engraving machine, and placing the polyester film coated with UV ink in step (3) on the machine table of the laser engraving machine for hundred-grid engraving; (5) After engraving is completed, 3M tape is evenly applied to the polyester film on which the 100 grids are engraved in step (4) and allowed to stand; then, a peeling machine is used to quickly peel off the grids with a constant force, and the adhesion level of the UV ink on the polyester film is evaluated by observing the ratio of the number of grids removed by the tape to the total number of grids.

2. The method for testing the adhesion of polyester film using UV ink coating according to claim 1, characterized in that: In step (2), the experimental temperature is 15-30° C. and the relative humidity is 40%-60%.

3. The method for testing the adhesion of polyester film using UV ink coating according to claim 1, characterized in that: The specific steps of the hundred-grid engraving method used in step (4) are as follows: design a hundred-grid pattern in the software of the laser engraving machine, the pattern consisting of ten horizontal lines and ten vertical lines, and the spacing between each line is uniform and 0.5 to 2 cm; the depth of the line engraving is the same as the scraping thickness to avoid scratching the polyester film, and finally a grid of 10×10 in the horizontal and vertical directions is formed, containing a total of 100 grids.

4. The method for testing the adhesion of polyester film using UV ink coating according to claim 1, characterized in that: The steps of the tape sticking and peeling process in step (5) are as follows: stick the 3M tape parallely and evenly on the cured UV ink polyester film, ensuring that the middle of the tape completely covers the engraved squares; use an eraser to rub the tape to apply pressure to ensure that it is evenly pasted and there is no air underneath; after pasting, wait for 30 to 120 seconds to ensure that the tape and the film are fully bonded; use the clamp of the peeling machine to fix the free end of the tape and the polyester film not coated with UV ink, and quickly remove the tape at an angle of 180° and apply a force of 150 to 200N.

5. The method for testing the adhesion of polyester film using UV ink coating according to claim 1, characterized in that: In step (5), the adhesive tape is one of 3M600, 3M610, Nichiban Tape, and P99 Tape. To avoid errors, the same batch of adhesive tape is used in each experiment.

6. The method for testing the adhesion of polyester film using UV ink coating according to claim 1, characterized in that: In step (3), the UV curing machine is preheated for 15 to 90 seconds before use, and the polyester film coated with UV ink is placed in the UV curing machine for curing 1 to 3 times until the UV ink is completely dry.

7. The method for testing the adhesion of polyester film using UV ink coating according to claim 1, characterized in that: In step (3), the final thickness of the ink coating is 10 to 100 μm.

8. The method for testing the adhesion of polyester film using UV ink coating according to any one of claims 1 to 7, characterized in that: In step (5), the adhesion grade evaluation criteria are as follows: 5B grade polyester film: There is no shedding of UV ink on the edges of all grid areas; 4B grade polyester film: UV ink on the edges of the grids in the grid area has peeling phenomenon, and the peeling rate is ≤5%; 3B grade polyester film: UV ink on the edges of the grids in the grid area has peeling phenomenon, 5%<peeling ratio≤15%; 2B grade polyester film: large pieces of UV ink fell off at the edges of the grids in the grid area, and some grids fell off in pieces, with a shedding ratio of 15% < ≤ 35%; 1B grade polyester film: large pieces of UV ink fell off at the edges of the grids in the grid area and some grids fell off completely, with a shedding ratio of 35% < ≤ 65%.

Citation Information

Patent Citations

  • Equipment for testing neodymium-iron-boron cross-grid through laser and operation method

    CN117214080A

  • Polyester film coating and pre-coated UV (ultraviolet) reinforced polyester film obtained by coating polyester film coating

    CN117659845A

  • Method and system for detecting adhesive force of printing ink of plastic cup

    CN117782972A

  • Adhesive tape stripping machine

    CN210286215U

  • Adhesive tape peeling machine

    JP2010123903A